2019
DOI: 10.1038/s41467-018-08065-1
|View full text |Cite
|
Sign up to set email alerts
|

Fetal-derived macrophages dominate in adult mammary glands

Abstract: Macrophages serve multiple functions including immune regulation, morphogenesis, tissue homeostasis and healing reactions. The current paradigm holds that mammary gland macrophages first arise postnatally during the prepubertal period from the bone marrow-derived monocytes. Here we delineate the origins of tissue-resident mammary gland macrophages using high-dimension phenotypic analyses, cell-fate mapping experiments, gene-deficient mice lacking selective macrophage subtypes, and antibody-based depletion stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 45 publications
7
81
0
Order By: Relevance
“…As expected (Sasmono et al, 2003), Mφs were also present in the embryonic liver at this 139 stage ( Fig. 1B), and it has been suggested that these fetal liver-derived Mφs contribute extensively to 140 the pool of tissue Mφs present in the adult gland (Jäppinen et al, 2019). Our data show that Mφs were 141 positioned adjacent to the embryonic mammary epithelium around the time of lineage segregation 142 (Lilja et al, 2018;Wuidart et al, 2018).…”
Section: Immunohistochemistry (Ffpe Slides)supporting
confidence: 73%
“…As expected (Sasmono et al, 2003), Mφs were also present in the embryonic liver at this 139 stage ( Fig. 1B), and it has been suggested that these fetal liver-derived Mφs contribute extensively to 140 the pool of tissue Mφs present in the adult gland (Jäppinen et al, 2019). Our data show that Mφs were 141 positioned adjacent to the embryonic mammary epithelium around the time of lineage segregation 142 (Lilja et al, 2018;Wuidart et al, 2018).…”
Section: Immunohistochemistry (Ffpe Slides)supporting
confidence: 73%
“…Thus, a key population of CD206+ macrophages are reciprocally regulated by ACKR2 and 228 CCR1. Importantly, CD206+ mammary gland macrophages have previously been implicated 229 in branching morphogenesis (Jäppinen et al, 2019) and we propose that ACKR2 and CCR1 230 reciprocally control this population to coordinate branching morphogenesis in the pubertal 231 mammary gland. 232 233 CCL7 regulates CD206+ macrophages and branching morphogenesis.…”
Section: Gland 207mentioning
confidence: 82%
“…derived macrophages(Jäppinen et al, 2019). Branching is severely impaired in these mice 289 suggesting that foetal-derived macrophages play a key role in promoting branching 290 morphogenesis(Jäppinen et al, 2019).…”
mentioning
confidence: 99%
“…These cell types all have immune-regulatory functions. In addition, specific tissue-resident MФs display self-renewal independent of AGM-HSC bone marrow-derived monocytes [23,86]. Gaucher disease, Alzheimer, Mendelian) and, to a lesser extent, for cellular therapy purposes [81][82][83][84].…”
Section: Myelopoiesismentioning
confidence: 99%
“…The interesting origin of tissueresident MФs such as microglia, kupffer cells and mammary gland MФs has been (genetically) tracked to early yolk sac and fetal myelopoiesis [85]. In addition, specific tissue-resident MФs display self-renewal independent of AGM-HSC bone marrow-derived monocytes [23,86]. The implication of these data for cellular therapy is that such embryonically derived MФs can be generated by culture systems that recapitulate embryonic development, such as iPSCs.…”
Section: Myelopoiesismentioning
confidence: 99%